The distorted and mispronounced debate about gender intolerance in social public spaces educationals / O debate distorcido e mal pronunciado sobre a intolerância de gênero nas ágoras sociais - escolas - Filipe Torres de Melo; Kaline Pacífico de Araújo Santos (Universidade Estadual de Alagoas, 2019)
In the educational context, intolerance involving minorities, especially nonheteronormative ones, has shown to be of great worldwide relevance due to the fact that it has undergone constant changes, being positive or negative and often independent of popular acceptance, generating a series of phenomena, which later resulted in a series of laws and guarantees in the contemporary world. In light of this, several philosophers, such as Michel Focault and Paulo Freire, have devoted themselves to writing works on the function of school within the social body, since it plays a fundamental role as a constructive, cohesive and harmonious agent. For this reason, there is a need to study the progress of homoaffective minorities in relation to their experience within the Brazilian educational system, as well as the challenges of living with those who see inequality as a negative factor, something that is reflected both in learning and in the social relations of the learner. Moreover, as far as methodological aspects are concerned, this work is of an applied nature, in accordance with the exploratory and descriptive objectives, in addition, with regard to technical procedures, bibliographical and documentary sources are integrated into the work.